2020
DOI: 10.1093/gbe/evaa020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of the Cthrc1 Genes, a Newly Defined Collagen-Like Family

Abstract: Collagen triple helix repeat containing protein 1 (Cthrc1) is a secreted glycoprotein reported to regulate collagen deposition and to be linked to the Transforming growth factor β/Bone morphogenetic protein and the Wnt/planar cell polarity pathways. It was first identified as being induced upon injury to rat arteries and was found to be highly expressed in multiple human cancer types. Here, we explore the phylogenetic and evolutionary trends of this metazoan gene family, previously studied only in vertebrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Glycosylated protein CTHRC1 with a signal sequence is related to ECM and contains a variable short collagen-like motif. Intriguingly, CTHRC1 plays a role in inhibiting structural proteins, unlike other members of the collagen family [1,16]. Moreover, Leclair et al found that Cthrc1 cleaved at the N-terminus by plasmin shows better inhibition of collagen synthesis compared to full-length Cthrc1 in the PAC1 cell line [17].…”
Section: The Structural Characteristics and Expression Of Cthrc1mentioning
confidence: 99%
“…Glycosylated protein CTHRC1 with a signal sequence is related to ECM and contains a variable short collagen-like motif. Intriguingly, CTHRC1 plays a role in inhibiting structural proteins, unlike other members of the collagen family [1,16]. Moreover, Leclair et al found that Cthrc1 cleaved at the N-terminus by plasmin shows better inhibition of collagen synthesis compared to full-length Cthrc1 in the PAC1 cell line [17].…”
Section: The Structural Characteristics and Expression Of Cthrc1mentioning
confidence: 99%
“…This study in carefully examining the role of the matrisome across cancers, has identified CTHRC1 and LOXL2 as major ECM regulators across cancers. Both play a role in collagen synthesis and assembly [23,28] by possibly interacting with POSTN, MMP13, SFRP4, COL11A1, COL10A1, COL1A1, ADAMTS12 and PPAPDCA1. This suggests the regulation of collagen could be a vital pan-cancer mediator of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…CTHRC1 and LOXL2 are both also known regulators of collagen synthesis and assembly [23,28]. Collagen makes up at least 30% of the total protein in the human body [29] and is highly aligned and anisotropic contributing to tumor cell survival and metastasis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The human protein contains an N-terminal hydrophobic signal peptide of 30 amino acids in length that directs CTHRC1 for secretion, a short collagen triple helix repeat (CTHR) domain consisting of 12 repeats of the Gly-X-Y motif located between amino acids 57 and 93 [ 12 ], and a highly conserved C-terminal domain with structural homology to the globular C1q domain of collagens VIII and X domain ( Figure 1 ) [ 13 ]. The CTHR domain may promote CTHRC1 dimer or trimer formation and mediate interaction with a variety of ligands [ 12 , 13 ]. The domain structure of CTHRC1 is similar to that of adiponectin, which belongs to the C1q/tumor necrosis factor (TNF)-related protein superfamily [ 14 ].…”
Section: Cthrc1 Domain Structurementioning
confidence: 99%